FAKTOR- FAKTOR UTAMA PEMBENTUK PREFERENSI MASYARAKAT MENYIKAPI PELEBARAN JALAN H.M. SUWIGNYO TERHADAP PROSPEK ASET PRIBADI - Muhammad Hidayat; Fery Kurniadi (Jurnal Teknik Sipil dan Perencanaan)
The broadening of H.M. Suwignyo Street have triggered the street corridor expansion. The property's owners take benefit from the increasing of asset value. They will have choices to manage and determine preferences for the asset. This study was aimed to find out the prominent factors that determine asset's owner preferences toward street broadening consequences. In first phase, analysis is performed qualitatively to construct the quantitative instruments for next research. Data are gathered from observation and semi-structured interview to informans. Data are categorised and codified with the result as initial hypotheses, which indicate community preferences to employ the property asset. The result showed that the social strata of asset's owner; asset tangible and intangible value comprehension; economic motif; gentrification; and the intervening factor/ government role are the prominent factors